Análise da literatura das humanidades digitais: uma proposta bibliométrica para descrição de seu escopo e congruência conceitual - Castro, Renan Marinho de (2020)
This study aims to build and visualize bibliometric maps from a literature review on digital humanities. The main objective of this research was to elaborate a mapping of the field through the construction of graphs for analysis of bibliometrics metrics. A reading of these data was implemented using the VOSviewer software to build a diagnosis of the scope of digital humanities. The analysis focused on the data which provide subsidies for a thematic-conceptual description and the domain of digital humanities when analyzing keywords, authors and journals. It seeks a sensitive notion of what can reveal the influence of the production of academic literature on the composition of digital humanities. It applies an analysis based on three pillars of bibliometric studies: authors, journals and keywords of retrieved academic articles. It outlines a scope analysis of the digital humanities domain based on bibliometric research. It clarifies the constitution of an incipient and complex domain through the analysis of the characteristics printed in the literature and only through it available. It combines concepts about bibliometric approaches with analysis based on visualization tools, legitimizing practices concerning digital humanities as a tool for knowledge of the field itself. It pursues a categorization capable of not only revealing details of its scope, but also providing elements indicative of which themes influence the area. It indicates the influence of other disciplines in the digital humanities and visualizes clearly which terms appear with greater recurrence. It lists the most recurrent terms in the literature, breaking down this list into terms indicated by the authors and those indicated by the database indexes. It compares these data in order to achieve a thematic-conceptual expressiveness of a field considered interdisciplinary and hybrid. It categorizes the product of these data to conclude, in addition to an organic thematic-conceptual description, a diagnosis of the digital humanities domain.